2004
DOI: 10.1023/b:bigi.0000034426.31105.da
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Structure of Oreochromis spp. (Tilapia) Populations in Malaysia as Revealed by Microsatellite DNA Analysis

Abstract: The genetic make-up of five populations of Oreochromis spp. was examined by microsatellite analysis. Eleven polymorphic microsatellite loci showed significant departures from the Hardy-Weinberg equilibrium. The mean heterozygosity ranged from 0.6280 to 0.7040 for each population. The genetic distance values showed a clear separation between O. niloticus and O. mossambicus. The differentiation of the O. niloticus populations was then tested with various genetic measures, which are based on both the Infinite All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 14 publications
3
9
1
Order By: Relevance
“…Bhassu et al (2004) also observed such heterozygote deficits at 11 microsatellite loci (different than those used here) in their domesticated or feral samples of O. niloticus and O. mossambicus from Malaysia. All these different cases render the "null alleles" hypothesis unlikely.…”
Section: Discussionsupporting
confidence: 46%
“…Bhassu et al (2004) also observed such heterozygote deficits at 11 microsatellite loci (different than those used here) in their domesticated or feral samples of O. niloticus and O. mossambicus from Malaysia. All these different cases render the "null alleles" hypothesis unlikely.…”
Section: Discussionsupporting
confidence: 46%
“…Genetic identities of the four populations I = 0.6946-0.9416 (genetic distance D s = 0.0602-0.3644) were close to that of different populations in one species (populations in one species I = 0.80-0.97, genetic distance D s = 0.03-0.20) (Thorp 1982), larger in I (I = 0.008-0.458) and less in D s (D s = 0.542-0.992) that of tilapia populations in Malaysia, as reported by Bhassu, Yusoff, Panandam, Embong, Oyyan and Tan (2004). The genetic identity value of different populations in the same species should be large.…”
Section: Discussionsupporting
confidence: 86%
“…This finding seems to be species-specific: other fishes showed a large number of alleles for each locus in each of the studied populations (Balloux and Lugon-Moulin, 2002;Liu and Cordes, 2004), as, for example, brown trout, Salmo trutta (Hansen et al, 2000), Salvelinus fontinalis (Wilson et al, 2004) or Thymmalus thymmalus (Gum et al, 2003). Nevertheless, deviations from the Hardy-Weinberg equilibrium is frequent in fish populations (Poteaux et al, 1999;Bhassu et al, 2004).…”
Section: Discussionmentioning
confidence: 81%